Empowering Elderly Exercise Groups in Gout Arthritis Management Through Education and Ergonomic Exercise - Himmatul Ulya; Erni setiyorini; Sandi Alfa Wiga Arsa; Anita Rahmawati (Health Gate, 2026)
Gout arthritis is one of the health problems commonly experienced by the elderly and can cause joint pain and limited activity if not managed properly. Lack of knowledge about gout arthritis management is a factor that can worsen the condition. Therefore, education about gout arthritis management and ergonomic exercise is needed as a non-pharmacological management effort that can be done independently. The purpose of this community service program was to increase the knowledge of the elderly exercise group in managing gout arthritis through health education and demonstrations of ergonomic exercises as a promotive and preventive measure. The method used was a lecture providing education on gout arthritis management and ergonomic exercises using leaflets and demonstrations of ergonomic exercises. The target of the activity was members of the elderly exercise group in Bacem Village, Ponggok District, Blitar Regency. The pre-test results showed that 70% of participants were in the adequate knowledge category, and 30% were in the good knowledge category. After the education was provided, the post-test results showed an increase in knowledge, with 85% in the good knowledge category and 15% in the adequate knowledge category. The results of the gout examination showed that 50% of participants had normal gout levels, 45% had high gout levels, and 5% had low gout levels. Education on gout arthritis management and ergonomic exercise proved to be effective in increasing the knowledge of the elderly and is recommended to be implemented continuously in promotive and preventive efforts in the community.